Chronic Circadian Rhythm Disturbance Accelerates Knee Cartilage Degeneration in Rats Accompanied by the Activation of the Canonical Wnt/β-Catenin Signaling Pathway - Song, Xiaopeng; Ma, Tianwen; Hu, Hailong; Zhao, Mingchao; Bai, Hui; Wang, Xinyu; Liu, Lin; Li, Ting; Sheng, Xuanbo; Xu, Xinyu; Zhang, Xinmin; Gao, Li (Frontiers in Pharmacology, 2021)
With the gradual deepening of understanding of systemic health and quality of life, the factors affecting osteoarthritis (OA) are not limited to mechanical injury, metabolic abnormality, age and obesity, etc., but circadian rhythm, which play a non-negligible role in human daily life. The purpose of this study was to explore the molecular mechanism of chronic circadian rhythm disturbance (CRD) inducing cartilage OA-like degeneration. Rats with the anterior cruciate ligament excision transection (ACLT) were used to establish the early-stage OA model (6-week). The light/dark (LD) cycle shifted 12 h per week for 22 weeks in order to establish a chronic CRD model. BMAL1 knockdown (KD) and Wnt/β-catenin pathway inhibition was performed in chondrocytes. The contents of proinflammatory factors and OA biomarkers in serum and chondrocyte secretions were detected by ELISA. Pathological and immunohistochemical staining of articular cartilage indicated the deterioration of cartilage. WB and qPCR were used to evaluate the relationship between matrix degradation and the activation of Wnt/β-catenin signaling pathway in chondrocytes. We found that chronic CRD can cause OA-like pathological changes in knee cartilage of rats, accelerating cartilage matrix degradation and synovial inflammation. The expression of MMP-3, MMP-13, ADAMTS-4, and β-catenin increased significantly; BMAL1, Aggrecan, and COL2A1 decreased significantly in either LD-shifted cartilage or BMAL1-KD chondrocytes. The expression of β-catenin and p-GSK-3β elevated, while p-β-catenin and GSK-3β diminished. The inhibitor XAV-939 was able to mitigated the increased inflammation produced by transfected siBMAL1. Our study demonstrates that chronic CRD disrupt the balance of matrix synthesis and catabolic metabolism in cartilage and chondrocytes, and it is related to the activation of the canonical Wnt/β-catenin signaling pathway.